2021
DOI: 10.1039/d1nr04015d
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of exosomal-markers in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a worldwide malignancy with high mortality rates and poor prognosis due to the lack of effective biomarkers for early detection. Exosomes have been extensively...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Here, a widely targeted metabolic profiling was first performed based on the LC-ESI-MS/MS platform to obtain the sEVs’ chemical signatures, and a total of 344 metabolites were identified with various categories including organic acid and their derivatives, amino acid, benzene, and substituted derivatives, alcohol and amines, heterocyclic compounds, nucleosides and their derivatives, aldehyde, ketones, esters, and so forth (Figure b). Owing to the combined treatments of the TiO 2 beads for EV capture with the 30 kDa membrane for ultrafiltration, most metabolites should be carried by EV particles rather than freely dissociated in plasma, even though there is an absence of an EV metabolome database for source tracking . Besides, lipid subclass (e.g., glycerophospholipids, fatty acyls, glycerolipids, and sphingolipids) could also be detected in our studies because of the use of 70% methanol as a solvent in metabolic analysis.…”
Section: Resultsmentioning
confidence: 93%
“…Here, a widely targeted metabolic profiling was first performed based on the LC-ESI-MS/MS platform to obtain the sEVs’ chemical signatures, and a total of 344 metabolites were identified with various categories including organic acid and their derivatives, amino acid, benzene, and substituted derivatives, alcohol and amines, heterocyclic compounds, nucleosides and their derivatives, aldehyde, ketones, esters, and so forth (Figure b). Owing to the combined treatments of the TiO 2 beads for EV capture with the 30 kDa membrane for ultrafiltration, most metabolites should be carried by EV particles rather than freely dissociated in plasma, even though there is an absence of an EV metabolome database for source tracking . Besides, lipid subclass (e.g., glycerophospholipids, fatty acyls, glycerolipids, and sphingolipids) could also be detected in our studies because of the use of 70% methanol as a solvent in metabolic analysis.…”
Section: Resultsmentioning
confidence: 93%
“…Most of these studies identified diagnostic biomarkers by collecting samples from cancer versus control, 21,41,[50][51][52][53][54][55][56] or pre-versus post-operation. 57 Meanwhile, there were also studies focusing on prognosis 31,[58][59][60][61] or prediction of response to treatment. [62][63][64][65]…”
Section: Ms-based Metabolomics and Lipidomics In Ev Studiesmentioning
confidence: 99%
“…Among all detected metabolite categories in serum EVs from esophageal squamous cell carcinoma (ESCC) patients, organic acids (OAs) and their derivatives were the most abundant, which accounts for 16.41%. 59 As a particular group of metabolites, OAs consist of many intermediate metabolites of critical metabolic pathways, such as the tricarboxylic acid cycle (TCA) and glycolysis. 73 The status of the TCA cycle in cancer cells is different from normal cells.…”
Section: Organic Acidsmentioning
confidence: 99%
“…urine is most favorable for point‐of‐care testing (POCT) that is a powerful platform for home testing, which enables individuals to monitor their health status through frequent diagnosis at their homes so that diseases can be diagnosed at the earliest possible time‐point 3,4 . In particular, it is worthy of noting that a variety of cancer markers (e.g., engrailed‐2 protein [EN2] 5 or prostate‐specific antigen [PSA] 6 for prostate cancer, bladder cancer‐specific nuclear matrix protein‐4 [BCLA‐4] 7 for BCa, kidney injury molecule‐1 [KIM‐1] 8 for renal cancer, human epididymis protein 4 [HE4] 9 for ovarian cancer, trefoil factor [TFF1] 10 for pancreatic cancer, a disintegrin and metalloprotease domain 12 [ADAM12] 11 for gastric cancer, leucine‐rich‐alpha2‐glycoprotein 1 [LRG1] 12,13 for lung cancer, etc .) have been found in urine, and thus urine holds a great potential for POCT‐based, precise in vitro cancer diagnosis 14–16 .…”
Section: Introductionmentioning
confidence: 99%